Democratizing inequalities : dilemmas of the new public participation - Lee, Caroline W.; McQuarrie, Michael; Walker, Edward T.; Calhoun, Craig J., 1952- (New York University Press, 2015)
"Opportunities to "have your say," "get involved," and "join the conversation" are everywhere in public life. From crowdsourcing and town hall meetings to government experiments with social media, participatory politics increasingly seem like a revolutionary antidote to the decline of civic engagement and the thinning of the contemporary public sphere. Many argue that, with new technologies, flexible organizational cultures, and a supportive policymaking context, we now hold the keys to large-scale democratic revitalization. Democratizing Inequalities shows that the equation may not be so simple. Modern societies face a variety of structural problems that limit potentials for true democratization, as well as vast inequalities in political action and voice that are not easily resolved by participatory solutions. Popular participation may even reinforce elite power in unexpected ways. Resisting an oversimplified account of participation as empowerment, this collection of essays brings together a diverse range of leading scholars to reveal surprising insights into how dilemmas of the new public participation play out in politics and organizations. Through investigations including fights over the authenticity of business-sponsored public participation, the surge of the Tea Party, the role of corporations in electoral campaigns, and participatory budgeting practices in Brazil, Democratizing Inequalities seeks to refresh our understanding of public participation and trace the reshaping of authority in today's political environment"--